Bodies in Balance The Art of Tibetan Medicine - Hofer, Theresia (University of Washington Press, 2017)
2015 Best Art Book Accolade, ICAS Book Prize in the Humanities Category Bodies in Balance: The Art of Tibetan Medicine is the first comprehensive, interdisciplinary exploration of the triangular relationship among the Tibetan art and science of healing (Sowa Rigpa), Buddhism, and arts and crafts. This book is dedicated to the history, theory, and practice of Tibetan medicine, a unique and complex system of understanding body and mind, treating illness, and fostering health and well-being. Sowa Rigpa has been influenced by Chinese, Indian, and Greco-Arab medical traditions but is distinct from them. Developed within the context of Buddhism, Tibetan medicine was adapted over centuries to different health needs and climates across the region encompassing the Tibetan Plateau, the Himalayas, and Mongolia. Its focus on a holistic approach to health has influenced Western medical thinking about the prevention, diagnoses, and treatment of illness. Generously illustrated with more than 200 images, Bodies in Balance includes essays on contemporary practice, pharmacology and compounding medicines, astrology and divination, history and foundational treatises. The volume brings to life the theory and practice of this ancient healing art.